2021
DOI: 10.5001/omj.2021.112
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Its Correlate Among Children with Epilepsy at Single-center Study in Oman

Abstract: Objectives:Epilepsy is the most common neurological disorder in children and comorbid depression is common. This study aimed to assess the frequency of depressive symptoms along with demographic and clinical factors in children diagnosed with epilepsy in a tertiary care institution in Oman. Methods:This cross-sectionalstudy was conducted between June 2016 and August 2018 and constituted children (n=75) with age group from 6 to 12 years old, attending the epilepsy clinic at a tertiary care center during the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Similar results were found in a recent study, conducted in Oman, with 75 children with epilepsy, aged 6–12 years ( 21 ). The authors found that younger children had difficulty expressing their mood and sadness, reporting fewer depressive symptoms, which were represented by irritability, anger, and sleep disturbances.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were found in a recent study, conducted in Oman, with 75 children with epilepsy, aged 6–12 years ( 21 ). The authors found that younger children had difficulty expressing their mood and sadness, reporting fewer depressive symptoms, which were represented by irritability, anger, and sleep disturbances.…”
Section: Discussionsupporting
confidence: 91%
“…According to a study conducted in China, the psychological resilience of the first child was found to be significantly lower than that of the only child [36]. Although there was no relationship between the number of siblings and psychological resilience in our study, more detailed results can be obtained by adding the parameters of one child and first child (Table 4).…”
Section: Discussionmentioning
confidence: 44%